Personality traits and anxiety in patients with temporomandibular disorders - Atefeh Hekmati; Nazanin Mortazavi; Rahman Berdi Ozouni-Davaji; Mohammadali Vakili (BMC Psychology, 2022)
Abstract Background Temporomandibular disorders (TMD) have long been suggested to result from psychological factors. Recent studies, however, tend to consider TMD a chronic psychosomatic illness. The present study was designed to explore the association between TMD and personality profile. The Minnesota Multiphasic Personality Inventory-2-Reconstructed form (MMPI-2-RF) was used to evaluate the association for the first time. Methods A total of 258 subjects participated in this case–control study. TMD cases as detected by the Helkimo index were questioned regarding their personality characteristics and anxiety levels using MMPI-2-RF and Spielberger state and trait anxiety inventory. Results Patients with TMD scored higher on all personality characteristics except for Aberrant Experiences. The psychological profile of TMD showed no significant difference between theoretical and experimental Ideas of Persecution means. Patients with TMD reported significantly higher mean levels of state and trait anxiety than controls. The most frequently found anxiety levels in TMD cases have been mild state and trait anxiety (77.5% versus 74.4%). Conclusion Personality characteristic scores were considerably higher in TMD patients. TMD cases detected by Helkimo index manifest both trait and state anxiety as common findings.